Water-based formaldehyde-free woodworking glue and preparation method thereof
Through the combination of modified polyacrylate and modified silica, prepare a hydrophilic formaldehyde woodworking, solve the problem of insufficient combustion, antibacterial and water resistance in the existing technologies, and achieve multi -performance Improvement.
Patent Information
- Application Number
- CN202411739811.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, water-based woodworking glue has shortcomings in flame retardant, antibacterial and water resistance, and it is difficult to meet the application needs of various performance requirements.
By using modified polyacrylate and modified silicon dioxide, combined with emulsifiers, emulsifiers, and photoretinants to prepare a hydrophilin -free wooden gum. The adhesive improves its flame retardant, antibacterial and water resistance by introducing silicon hydrogen, phosphorus and seasonal salt structure.
The good flame retardant, antibacterial and water resistance of woodworking gums have been realized, and their application areas have been expanded, and they have met a variety of performance requirements.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of woodworking glue, in particular to a water-based formaldehyde-free woodworking glue and a preparation method thereof. Background Art
[0002] Wood glue is a kind of adhesive specially used for bonding wood and wood products. It plays a vital role in furniture manufacturing, wood product processing, building decoration and other scenarios. There are many types of wood glue, including water-based glue and solvent-based glue. Water-based glue, such as white latex and polyurethane wood glue, has good environmental protection and water resistance; solvent-based glue may contain certain organic solvents, but its viscosity and strength may also be higher.
[0003] In different application scenarios, wood glue needs to meet different performance requirements, such as flame retardant properties to prevent fire accidents, antibacterial properties to prevent bacteria from growing and spreading, and water resistance to prevent moisture from affecting the bonding effect. Therefore, the application field of wood glue with multiple properties has been greatly expanded. Summary of the invention
[0004] The purpose of the present invention is to provide a water-based formaldehyde-free wood glue and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The invention discloses a water-based formaldehyde-free woodworking glue, which is obtained by mixing modified polyacrylate, modified silicon dioxide, an emulsifier, a defoamer, pure water and a photoinitiator.
[0007] Preferably, the modified polyacrylate is obtained by using n-butyl lithium as an initiator to initiate polymerization of cyclosiloxane and acrylate monomers, and then end-capping with dimethylchlorosilane to obtain a pre-modified polyacrylate, reacting with vinyl diphenylphosphine and then reacting with 3-(4-bromophenyl)-1-propylene.
[0008] Preferably, the silicon dioxide is obtained by reacting silicon dioxide modified with 4-(trimethoxysilyl)butyraldehyde with chitosan and then with thioglycolic acid.
[0009] A method for preparing water-based formaldehyde-free woodworking glue comprises the following preparation steps:
[0010] (1) Under anhydrous and oxygen-free, nitrogen-protected conditions, 1.5 mol / L n-butyl lithium-n-hexane solution and tetrahydrofuran are mixed, cyclosiloxane is added at -5-0°C, stirred for 30 minutes, heated to 30-40°C, reacted for 5-6 hours, heated to 50-60°C, acrylate monomer is added, reacted for 5-6 hours, then heated to 70-80°C, dimethylchlorosilane is added, refluxed for 1-2 hours, after the reaction is completed, the filtrate is filtered and retained, and vacuum dried by reduced pressure rotary evaporation to obtain pre-modified polyacrylate;
[0011] (2) pre-modified polyacrylate, vinyl diphenylphosphine, chloroplatinic acid, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.8-1.0):(0.1-0.2):(20-30), heated to 90-100° C. for reaction for 10-12 h, and vacuum dried by rotary evaporation to obtain phosphorus-containing polyacrylate;
[0012] (3) mixing phosphorus-containing polyacrylate, 3-(4-bromophenyl)-1-propylene, and acetonitrile in a mass ratio of 1:(0.2-0.3):(20-30), heating to 100° C. and reflux reaction for 10-12 h, and vacuum drying by rotary evaporation to obtain modified polyacrylate;
[0013] (4) mixing chitosan-modified silica, 0.1 mol / L acetic acid solution, thioglycolic acid, and p-toluenesulfonic acid in a mass ratio of 1:(40-50):(15-20):(0.05-0.08), reacting at 25-30° C. for 24 h, filtering and washing with pure water for 3-4 times, and vacuum drying to obtain modified silica;
[0014] (5) Modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator are mixed, and emulsified at a speed of 16 kr / min using a high-speed homogenizing emulsifier to obtain water-based formaldehyde-free woodworking glue.
[0015] Preferably, the mass ratio of the 1.5 mol / L n-butyl lithium-n-hexane solution, tetrahydrofuran, cyclosiloxane, acrylate monomer and dimethylchlorosilane in step (1) is 1:(10-12):(1-2):(4-5):(0.4-0.6).
[0016] Preferably, the cyclosiloxane in step (1) is tetramethylcyclotetrasiloxane; and the acrylate monomer is a mixture of acrylic acid and vinyl acetate in a mass ratio of 1:(2-3).
[0017] Preferably, the preparation method of the chitosan-modified silica in step (4) is as follows: 4-(trimethoxysilyl)butyraldehyde, anhydrous ethanol and pure water are mixed in a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of 4-(trimethoxysilyl)butyraldehyde in silica is added, the temperature is raised to 110°C, reflux reaction is carried out for 3-4 hours, filtering and washing with anhydrous ethanol 4 times, and vacuum drying to obtain pretreated silica; chitosan and 2wt% acetic acid solution are mixed in a mass ratio of 1:40, the temperature is raised to 60°C, 0.2-0.3 times the mass of chitosan in pretreated silica is added, the temperature is raised to 90°C and the reaction is continued for 2 hours, filtering and washing with ethanol 3-4 times, and vacuum drying to obtain chitosan-modified silica.
[0018] Preferably, the emulsifier model in step (5) is MS-1; the defoamer model is Surfynol DF-110C; and the photoinitiator is 651 photoinitiator.
[0019] Preferably, the amount of the modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator in step (5) is: by mass, 100 parts of modified polyacrylate, 3-5 parts of modified silica, 10-12 parts of emulsifier, 2-3 parts of defoamer, 40-50 parts of pure water and 1-2 parts of photoinitiator.
[0020] Preferably, the deacetylation degree of the chitosan is ≥93%; and the silicon dioxide model is VK-SP30S.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] When preparing the water-based formaldehyde-free woodworking glue, the present invention firstly uses n-butyl lithium as an initiator to initiate polymerization of cyclosiloxane and acrylate monomers, then uses dimethylchlorosilane to end-cap to obtain pre-modified polyacrylate, reacts the pre-modified polyacrylate with vinyl diphenylphosphine, and then reacts with 3-(4-bromophenyl)-1-propylene to obtain modified polyacrylate; secondly, reacts 4-(trimethoxysilyl)butyraldehyde-modified silicon dioxide with chitosan, and then reacts with thioglycolic acid to obtain modified silicon dioxide; finally, the modified polyacrylate, modified silicon dioxide, emulsifier, defoamer, pure water and photoinitiator are mixed to obtain the water-based formaldehyde-free woodworking glue.
[0023] Firstly, n-butyl lithium is used as an initiator to initiate polymerization of cyclosiloxane and acrylate monomers to obtain polyacrylate containing polysiloxane, wherein the polysiloxane can improve the water resistance and heat resistance of wood glue, and introduces silicon-hydrogen bonds, and then the polyacrylate is capped with dimethylchlorosilane to obtain pre-modified polyacrylate with silicon-hydrogen terminals; the pre-modified polyacrylate is reacted with vinyl diphenylphosphine, and phosphorus elements with flame retardant function are grafted on the pre-modified polyacrylate through double bonds and silicon-hydrogen addition, and the synergistic effect of phosphorus elements and silicon elements can further improve the flame retardant performance of wood glue, and then the pre-modified polyacrylate is reacted with 3-(4-bromophenyl)-1-propylene to generate a quaternary phosphonium salt structure with antibacterial function, and a double bond is introduced;
[0024] Secondly, the 4-(trimethoxysilyl)butyraldehyde-modified silica is reacted with chitosan. The surface of the 4-(trimethoxysilyl)butyraldehyde-modified silica contains aldehyde functional groups, which can react with the amino groups in chitosan to form a Schiff base to obtain chitosan-coated silica. Chitosan, as a natural material, is biodegradable and has good environmental protection. The silica surface is then reacted with thioglycolic acid to make it rich in thiol groups, which has a good viscosity-enhancing effect.
[0025] Finally, modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator are mixed to obtain water-based formaldehyde-free wood glue. The side chain of the modified polyacrylate has a double bond, and the surface of the modified silica has a thiol group. They can react in the presence of light and photoinitiator to form a cross-linked network, which can accelerate the curing speed and enhance the mechanical properties. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The emulsifier used in the following examples and comparative examples is of model MS-1; the defoamer is of model SurfynolDF-110C, the photoinitiator is 651 photoinitiator, the deacetylation degree of chitosan is ≥93%; and the silicon dioxide is of model VK-SP30S.
[0028] Embodiment 1:
[0029] A method for preparing a water-based formaldehyde-free woodworking glue, the method comprising the following preparation steps:
[0030] (1) Acrylic acid and vinyl acetate are mixed in a mass ratio of 1:2 to obtain an acrylate monomer; 1.5 mol / L n-butyl lithium-n-hexane solution, tetrahydrofuran, tetramethylcyclotetrasiloxane, acrylate monomer, and dimethylchlorosilane are weighed in a mass ratio of 1:10:1:4:0.4; under anhydrous and oxygen-free, nitrogen protection conditions, 1.5 mol / L n-butyl lithium-n-hexane solution and tetrahydrofuran are mixed, cyclosiloxane is added at 0°C and stirred for 30 minutes, the temperature is raised to 40°C, the reaction is carried out for 6 hours, the temperature is raised to 60°C, the acrylate monomer is added, the reaction is carried out for 6 hours, the temperature is raised to 80°C, dimethylchlorosilane is added, and the reaction is refluxed for 2 hours. After the reaction is completed, the filtrate is filtered and retained, and vacuum dried by reduced pressure rotary evaporation to obtain a pre-modified polyacrylate;
[0031] (2) pre-modified polyacrylate, vinyl diphenylphosphine, chloroplatinic acid, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.8:0.1:20, heated to 100° C. for reaction for 12 h, and vacuum dried by rotary evaporation to obtain phosphorus-containing polyacrylate;
[0032] (3) mixing phosphorus-containing polyacrylate, 3-(4-bromophenyl)-1-propylene, and acetonitrile in a mass ratio of 1:0.2:20, heating to 100° C. and reflux reaction for 12 h, and vacuum drying by rotary evaporation to obtain modified polyacrylate;
[0033] (4) 4-(trimethoxysilyl)butyraldehyde, anhydrous ethanol, and pure water were mixed at a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of 4-(trimethoxysilyl)butyraldehyde was added with silica, the temperature was raised to 110°C, refluxed for 4 hours, filtered and washed 4 times with anhydrous ethanol, and vacuum dried to obtain pretreated silica; chitosan and 2wt% acetic acid solution were mixed at a mass ratio of 1:40, heated to 60°C, 0.2 times the mass of chitosan pretreated silica was added, the temperature was raised to 90°C and the reaction was continued for 2 hours, filtered and washed 3 times with ethanol, and chitosan modified silica was obtained by vacuum drying; chitosan modified silica, 0.1 mol / L acetic acid solution, thioglycolic acid, and p-toluenesulfonic acid were mixed at a mass ratio of 1:40:15:0.05, reacted at 30°C for 24 hours, filtered and washed 4 times with pure water after the reaction was completed, and modified silica was obtained by vacuum drying;
[0034] (5) Weigh 100 parts of modified polyacrylate, 3 parts of modified silica, 10 parts of emulsifier, 2 parts of defoamer, 40 parts of pure water and 1 part of photoinitiator by mass, mix the modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator, and emulsify them with a high-speed homogenizer at a speed of 16 kr / min to obtain water-based formaldehyde-free woodworking glue.
[0035] Embodiment 2:
[0036] A method for preparing a water-based formaldehyde-free woodworking glue, the method comprising the following preparation steps:
[0037] (1) Acrylic acid and vinyl acetate are mixed in a mass ratio of 1:2.5 to obtain an acrylate monomer; 1.5 mol / L n-butyl lithium-n-hexane solution, tetrahydrofuran, tetramethylcyclotetrasiloxane, acrylate monomer, and dimethylchlorosilane are weighed in a mass ratio of 1:11:1.5:4.5:0.5; under anhydrous and oxygen-free, nitrogen protection conditions, 1.5 mol / L n-butyl lithium-n-hexane solution and tetrahydrofuran are mixed, cyclosiloxane is added at -3°C and stirred for 30 minutes, the temperature is raised to 35°C, the reaction is carried out for 5.5 hours, the temperature is raised to 55°C, the acrylate monomer is added, the reaction is carried out for 5.5 hours, the temperature is raised to 75°C, dimethylchlorosilane is added, and the reaction is refluxed for 1.5 hours. After the reaction is completed, the filtrate is filtered and retained, and vacuum dried by reduced pressure rotary evaporation to obtain a pre-modified polyacrylate;
[0038] (2) pre-modified polyacrylate, vinyl diphenylphosphine, chloroplatinic acid, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.9:0.15:25, heated to 95° C. for reaction for 11 h, and vacuum dried by rotary evaporation to obtain phosphorus-containing polyacrylate;
[0039] (3) mixing phosphorus-containing polyacrylate, 3-(4-bromophenyl)-1-propylene, and acetonitrile in a mass ratio of 1:0.25:25, heating to 100° C. and reflux reaction for 11 h, and vacuum drying by rotary evaporation to obtain modified polyacrylate;
[0040] (4) 4-(trimethoxysilyl)butyraldehyde, anhydrous ethanol, and pure water were mixed at a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of 4-(trimethoxysilyl)butyraldehyde was added with silica, the temperature was raised to 110°C, refluxed for 3.5 hours, filtered and washed 4 times with anhydrous ethanol, and vacuum dried to obtain pretreated silica; chitosan and 2wt% acetic acid solution were mixed at a mass ratio of 1:40, heated to 60°C, 0.25 times the mass of chitosan was added with pretreated silica, the temperature was raised to 90°C and the reaction was continued for 2 hours, filtered and washed 3 times with ethanol, and chitosan-modified silica was obtained by vacuum drying; chitosan-modified silica, 0.1 mol / L acetic acid solution, thioglycolic acid, and p-toluenesulfonic acid were mixed at a mass ratio of 1:45:17:0.07, reacted at 26°C for 24 hours, filtered and washed 3 times with pure water after the reaction was completed, and modified silica was obtained by vacuum drying;
[0041] (5) 100 parts of modified polyacrylate, 4 parts of modified silica, 11 parts of emulsifier, 2.5 parts of defoamer, 45 parts of pure water and 1.5 parts of photoinitiator are weighed by mass, and the modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator are mixed, and emulsified with a high-speed homogenizing emulsifier at a speed of 16 kr / min to obtain a water-based formaldehyde-free woodworking glue.
[0042] Embodiment 3:
[0043] A method for preparing a water-based formaldehyde-free woodworking glue, the method comprising the following preparation steps:
[0044] (1) Acrylic acid and vinyl acetate are mixed in a mass ratio of 1:3 to obtain an acrylate monomer; 1.5 mol / L n-butyl lithium-n-hexane solution, tetrahydrofuran, tetramethylcyclotetrasiloxane, acrylate monomer, and dimethylchlorosilane are weighed in a mass ratio of 1:12:2:5:0.6; under anhydrous and oxygen-free, nitrogen protection conditions, 1.5 mol / L n-butyl lithium-n-hexane solution and tetrahydrofuran are mixed, cyclosiloxane is added at -5°C and stirred for 30 minutes, the temperature is raised to 30°C, the reaction is carried out for 5 hours, the temperature is raised to 50°C, the acrylate monomer is added, the reaction is carried out for 5 hours, the temperature is raised to 70°C, dimethylchlorosilane is added, and the reaction is refluxed for 1 hour. After the reaction is completed, the filtrate is filtered and retained, and vacuum dried by reduced pressure rotary evaporation to obtain a pre-modified polyacrylate;
[0045] (2) pre-modified polyacrylate, vinyl diphenylphosphine, chloroplatinic acid, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.0:0.2:30, heated to 90° C. for reaction for 10 h, and vacuum dried by rotary evaporation to obtain phosphorus-containing polyacrylate;
[0046] (3) mixing phosphorus-containing polyacrylate, 3-(4-bromophenyl)-1-propylene, and acetonitrile in a mass ratio of 1:0.3:30, heating to 100° C. and reflux reaction for 10 h, and vacuum drying by rotary evaporation to obtain modified polyacrylate;
[0047] (4) 4-(trimethoxysilyl)butyraldehyde, anhydrous ethanol, and pure water were mixed at a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of 4-(trimethoxysilyl)butyraldehyde was added with silica, the temperature was raised to 110°C, refluxed for 3 hours, filtered and washed 4 times with anhydrous ethanol, and vacuum dried to obtain pretreated silica; chitosan and 2wt% acetic acid solution were mixed at a mass ratio of 1:40, heated to 60°C, 0.3 times the mass of chitosan pretreated silica was added, the temperature was raised to 90°C and continued to react for 2 hours, filtered and washed 4 times with ethanol, and vacuum dried to obtain chitosan-modified silica; chitosan-modified silica, 0.1 mol / L acetic acid solution, thioglycolic acid, and p-toluenesulfonic acid were mixed at a mass ratio of 1:50:20:0.08, reacted at 25°C for 24 hours, filtered and washed 4 times with pure water after the reaction was completed, and modified silica was obtained by vacuum drying;
[0048] (5) Weigh 100 parts of modified polyacrylate, 5 parts of modified silica, 12 parts of emulsifier, 3 parts of defoamer, 50 parts of pure water and 2 parts of photoinitiator by mass, mix the modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator, and emulsify them with a high-speed homogenizer at a speed of 16 kr / min to obtain water-based formaldehyde-free woodworking glue.
[0049] Comparative Example 1:
[0050] The preparation method of the water-based formaldehyde-free woodworking glue of Comparative Example 1 is different from that of Example 2 in that it does not contain steps (2) to (3), and step (1) is modified as follows: acrylic acid and vinyl acetate are mixed in a mass ratio of 1:2.5 to obtain an acrylate monomer; 1.5 mol / L of n-butyl lithium-n-hexane solution, tetrahydrofuran, tetramethylcyclotetrasiloxane, acrylate monomer, and dimethylchlorosilane are weighed in a mass ratio of 1:11:1.5:4.5:0.5; under anhydrous and oxygen-free, nitrogen protection conditions, 1.5 mol / L of n-butyl lithium-n-hexane solution and tetrahydrofuran are mixed, cyclosiloxane is added at -3°C and stirred for 30 minutes, the temperature is raised to 35°C, the reaction is carried out for 5.5 hours, the temperature is raised to 55°C, the acrylate monomer is added, the reaction is carried out for 5.5 hours, the temperature is raised to 75°C, dimethylchlorosilane is added, and the reaction is refluxed for 1.5 hours. After the reaction is completed, the filtrate is filtered and retained, and vacuum dried by reduced pressure rotary evaporation to obtain modified polyacrylate.
[0051] Comparative Example 2:
[0052] The preparation method of the water-based formaldehyde-free woodworking glue of Comparative Example 2 differs from that of Example 2 in that step (3) is not included, and step (2) is modified as follows: pre-modified polyacrylate, vinyl diphenylphosphine, chloroplatinic acid, and N,N-dimethylformamide are mixed in a mass ratio of 1:0.9:0.15:25, the temperature is raised to 95° C., the reaction is carried out for 11 hours, and the modified polyacrylate is obtained by vacuum drying by rotary evaporation under reduced pressure.
[0053] Comparative Example 3:
[0054] The preparation method of the water-based formaldehyde-free woodworking glue in Comparative Example 2 differs from that in Example 2 in that step (2) is modified as follows: 4-(trimethoxysilyl)butyraldehyde, anhydrous ethanol, and pure water are mixed in a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of 4-(trimethoxysilyl)butyraldehyde in silica is added, the temperature is raised to 110°C, refluxed for 3.5 hours, filtered and washed 4 times with anhydrous ethanol, and vacuum dried to obtain pretreated silica; chitosan and 2wt% acetic acid solution are mixed in a mass ratio of 1:40, heated to 60°C, 0.25 times the mass of chitosan in pretreated silica is added, the temperature is raised to 90°C and the reaction is continued for 2 hours, filtered and washed 3 times with ethanol, and vacuum dried to obtain modified silica.
[0055] Test Example 1:
[0056] Flame retardant performance test:
[0057] Test method: According to the standard GB / T2406.2-2009, the water-based formaldehyde-free woodworking glue prepared in the embodiment and the comparative example was tested for the limiting oxygen index. 15g of the adhesive was placed in a mold and heated at 1000mW / cm 2 The samples were irradiated under a high pressure mercury lamp and cured at 50°C. The results are shown in Table 1.
[0058] Table 1 Flame retardant performance test results
[0059] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.6 Comparative Example 1 22.7 Example 2 31.9 Comparative Example 2 31.0 Example 3 32.0 Comparative Example 3 31.1
[0060] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, it can be found that the water-based formaldehyde-free wood glue prepared by the present invention has good flame retardant properties.
[0061] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that n-butyl lithium is used as an initiator to initiate the polymerization of cyclosiloxane and acrylate monomers to obtain polyacrylate containing polysiloxane, and polysiloxane can improve the water resistance and heat resistance of wood glue, and introduce silicon-hydrogen bonds, and then end-cap with dimethylchlorosilane to obtain terminal silicon-hydrogen pre-modified polyacrylate; the pre-modified polyacrylate is reacted with vinyl diphenylphosphine, and phosphorus element with flame retardant function is grafted through double bonds and silicon-hydrogen addition. The synergistic effect of phosphorus element and silicon element can further improve the flame retardant properties of wood glue.
[0062] Test Example 2:
[0063] Antibacterial performance test:
[0064] Test method: The water-based formaldehyde-free woodworking glue prepared in the examples and comparative examples was placed in a 10 cm × 10 cm polytetrafluoroethylene mold and heated at 1000 mW / cm 2 Irradiate under a high-pressure mercury lamp, solidify at 50°C, and use a hole punch to take a 6mm circular slice; place the circular slice on an agar medium smeared with bacterial solution, turn it upside down in a constant temperature incubator at 37°C for culture, take it out after 24 hours to measure the diameter of the inhibition zone and record it. The bacterial solution selected Staphylococcus aureus, the larger the diameter, the better the antibacterial performance. The results are shown in Table 2.
[0065] Table 2 Antibacterial performance test results
[0066] Diameter of inhibition zone / mm Diameter of inhibition zone / mm Example 1 11.4 Comparative Example 1 5.9 Example 2 11.5 Comparative Example 2 6.0 Example 3 11.7 Comparative Example 3 9.3
[0067] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 2, it can be found that the water-based formaldehyde-free wood glue prepared by the present invention has good antibacterial properties.
[0068] The antibacterial properties of Examples 1 to 3 are better than those of Comparative Examples 1 to 2, indicating that n-butyl lithium is used as an initiator to initiate the polymerization of cyclosiloxane and acrylate monomers to obtain polyacrylate containing polysiloxane, and polysiloxane can improve the water resistance and heat resistance of wood glue, and introduce silicon-hydrogen bonds, and then end-cap with dimethylchlorosilane to obtain a pre-modified polyacrylate with terminal silicon-hydrogen; the pre-modified polyacrylate is reacted with vinyl diphenylphosphine, and a phosphorus element with flame retardant function is grafted by double bonds and silicon-hydrogen addition. The synergistic effect of phosphorus and silicon can further improve the flame retardant properties of wood glue, and then react with 3-(4-bromophenyl)-1-propylene to generate a quaternary phosphonium salt structure with antibacterial function.
[0069] Test Example 3:
[0070] Gluing performance test:
[0071] The plywood processed by the water-based formaldehyde-free woodworking glue prepared in the embodiment and the comparative example was tested for bonding strength; the bonding strength of the plywood was tested in accordance with the GB / T17657-2013 standard, wherein the wet bonding strength was tested in accordance with the national Class II plywood standard method, all plywoods were treated in a 90°C water bath for 3 hours, and then left to stand for 10 minutes to allow the surface water to dry before testing, and the tensile speed was 5 mm / min. The results are shown in Table 3.
[0072] Table 3 Gluing performance test results
[0073] Dry bonding strength (MPa) Wet bond strength (MPa) Example 1 2.01 1.56 Example 2 2.03 1.61 Example 3 2.04 1.64 Comparative Example 1 1.86 1.51 Comparative Example 2 1.85 1.50 Comparative Example 3 1.56 1.22
[0074] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 2, it can be found that the water-based formaldehyde-free woodworking glue prepared by the present invention has good gluing performance.
[0075] The gluing properties of Examples 1 to 3 are better than those of Comparative Example 3, indicating that n-butyl lithium is used as an initiator to initiate the polymerization of cyclosiloxane and acrylate monomers to obtain polyacrylate containing polysiloxane, and polysiloxane can improve the water resistance and heat resistance of woodworking glue; secondly, 4-(trimethoxysilyl)butyraldehyde-modified silica is reacted with chitosan, and the surface of 4-(trimethoxysilyl)butyraldehyde-modified silica contains aldehyde functional groups, which can react with amino groups in chitosan to form Schiff bases to obtain chitosan-coated silica, and chitosan is then reacted with thioglycolic acid to make the surface of silica contain abundant thiol groups, which has a good viscosity-increasing effect.
[0076] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A water-based formaldehyde-free wood glue, characterized in that: The water-based formaldehyde-free woodworking glue is obtained by mixing modified polyacrylate, modified silicon dioxide, emulsifier, defoamer, pure water and photoinitiator; The modified polyacrylate is obtained by using n-butyl lithium as an initiator to initiate polymerization of cyclosiloxane and acrylate monomers, and then end-capping with dimethylchlorosilane to obtain a pre-modified polyacrylate, reacting with vinyl diphenylphosphine and then reacting with 3-(4-bromophenyl)-1-propylene; The silicon dioxide is obtained by reacting silicon dioxide modified with 4-(trimethoxysilyl)butyraldehyde with chitosan and then with thioglycolic acid.
2. A method for preparing a water-based formaldehyde-free woodworking glue, characterized in that: The method comprises the following preparation steps: (1) Under anhydrous and oxygen-free, nitrogen-protected conditions, 1.5 mol / L n-butyl lithium-n-hexane solution and tetrahydrofuran are mixed, cyclosiloxane is added at -5-0°C, stirred for 30 minutes, heated to 30-40°C, reacted for 5-6 hours, heated to 50-60°C, acrylate monomer is added, reacted for 5-6 hours, then heated to 70-80°C, dimethylchlorosilane is added, refluxed for 1-2 hours, after the reaction is completed, the filtrate is filtered and retained, and vacuum dried by reduced pressure rotary evaporation to obtain pre-modified polyacrylate; (2) pre-modified polyacrylate, vinyl diphenylphosphine, chloroplatinic acid, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.8-1.0):(0.1-0.2):(20-30), heated to 90-100° C. for reaction for 10-12 h, and vacuum dried by rotary evaporation to obtain phosphorus-containing polyacrylate; (3) mixing phosphorus-containing polyacrylate, 3-(4-bromophenyl)-1-propylene, and acetonitrile in a mass ratio of 1:(0.2-0.3):(20-30), heating to 100° C. and reflux reaction for 10-12 h, and vacuum drying by rotary evaporation to obtain modified polyacrylate; (4) mixing chitosan-modified silica, 0.1 mol / L acetic acid solution, thioglycolic acid, and p-toluenesulfonic acid in a mass ratio of 1:(40-50):(15-20):(0.05-0.08), reacting at 25-30° C. for 24 h, filtering and washing with pure water for 3-4 times, and vacuum drying to obtain modified silica; (5) Modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator are mixed, and emulsified at a speed of 16 kr / min using a high-speed homogenizing emulsifier to obtain water-based formaldehyde-free woodworking glue.
3. The method for preparing a water-based formaldehyde-free wood glue according to claim 2, characterized in that: The mass ratio of the 1.5 mol / L n-butyl lithium-n-hexane solution, tetrahydrofuran, cyclosiloxane, acrylate monomer and dimethylchlorosilane in step (1) is 1:(10-12):(1-2):(4-5):(0.4-0.6).
4. The method for preparing a water-based formaldehyde-free wood glue according to claim 2, characterized in that: The cyclosiloxane in step (1) is tetramethylcyclotetrasiloxane; and the acrylate monomer is obtained by mixing acrylic acid and vinyl acetate in a mass ratio of 1:(2-3).
5. The method for preparing a water-based formaldehyde-free wood glue according to claim 2, characterized in that: The preparation method of the chitosan-modified silica in step (4) is as follows: 4-(trimethoxysilyl)butyraldehyde, anhydrous ethanol and pure water are mixed at a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of 4-(trimethoxysilyl)butyraldehyde of silica is added, the temperature is raised to 110°C, reflux reaction is carried out for 3-4 hours, filtering and washing with anhydrous ethanol for 4 times, and vacuum drying to obtain pretreated silica; chitosan and 2wt% acetic acid solution are mixed at a mass ratio of 1:40, the temperature is raised to 60°C, 0.2-0.3 times the mass of chitosan of pretreated silica is added, the temperature is raised to 90°C and the reaction is continued for 2 hours, filtering and washing with ethanol for 3-4 times, and vacuum drying to obtain chitosan-modified silica.
6. The method for preparing a water-based formaldehyde-free wood glue according to claim 2, characterized in that: The emulsifier model in step (5) is MS-1; the defoamer model is Surfynol DF-110C; and the photoinitiator is 651 photoinitiator.
7. The method for preparing a water-based formaldehyde-free wood glue according to claim 2, characterized in that: The amounts of the modified polyacrylate, modified silica, emulsifier, defoamer, pure water and photoinitiator in step (5) are as follows: by mass: 100 parts of modified polyacrylate, 3-5 parts of modified silica, 10-12 parts of emulsifier, 2-3 parts of defoamer, 40-50 parts of pure water and 1-2 parts of photoinitiator.
8. The method for preparing a water-based formaldehyde-free wood glue according to claim 5, characterized in that: The chitosan deacetylation degree is ≥93%; the silicon dioxide model is VK-SP30S.
Citation Information
Patent Citations
Adhesive set and bonding method using the same
CN101815770A
Preparation method of sulfhydryl-modified silica anti-mildew polyester coating
CN108192484A
Preparation method and application of hyperbranched block polymer copolymer
CN108707213A
Preparation method of wear-resistant coating for shell of circuit breaker
CN111019467A
Antibacterial deodorant tablet prepared from bio-based material and application thereof
CN113121854A
Cited By
Protective coating for limiting rope in aviation oxygen supply mask pipeline and preparation method of protective coating
CN120005464A
Dustproof anti-static artificial terrazzo and preparation method thereof
CN120247467A
Dustproof and antistatic artificial terrazzo and preparation method thereof
CN120247467B
Two-component high-frequency arc woodworking glue and preparation method thereof
CN121450261A